The economic burden of leprosy treatment to households in Ghana: A cross-sectional study in the Volta Region of Ghana - Maxwell Ayindenaba Dalaba; Alfred Kwesi Manyeh; Mustapha Immurana; Martin Amogre Ayanore; Isaiah Agorinya; James Akazili; Patricia Akweongo; Benedict Okoe Quao (SAGE Open Medicine)
Background: Despite the known detrimental socio-economic consequences of leprosy morbidity, disability and social exclusion at the household level, research investigating the precise economic burden of leprosy remains scarce. This study aims to address this gap by examining the socio-economic burden of leprosy in Ho municipality in the Volta Region of Ghana. Methods: This was a cross-sectional cost of illness study, and quantitative data were collected from leprosy patients between October and December 2023. Data collected included socio-demographic characteristics, direct and indirect costs related to treatment of leprosy from the patient’s perspective. Stata version 14 was used for the analysis. Results: A total of 35 respondents participated in the study, comprising 51.43% females and 48.57% males. All respondents (100%) reported having a valid National Health Insurance Scheme membership. The average total cost of leprosy treatment per patient, encompassing both direct and indirect expenses, was US$361.54 (SD ± 286.87). Disaggregating this cost further revealed a medical cost of US$44.30, a non-medical cost of US$47.07 and an indirect cost of US$290.16. The estimated annual household income of respondents was US$446.4 and 60% of respondents incurred expenditure that was more than 10% of their annual income and were deemed to have experienced catastrophic payment. Patients with sequelae incurred additional costs of US$46 (range: US$8.3–US$166.7) per case. Conclusion: The costs of treating leprosy were considerably high leading to catastrophic health payments. This highlights the need for an all-encompassing strategy that addresses medical, non-medical and indirect costs. Implementing targeted support programs and ensuring medication affordability are key steps towards mitigating the economic susceptibility of leprosy patients and facilitating successful treatment outcomes.